AN ANALYSIS OF THEME SYSTEM AND THEMATIC PROGRESSION OF UNDERGRADUATE STUDENTS' EXPOSITION TEXTS - SIHAB LAPOTO ADE POTRADINATA, - (2018)
The objectives of this study are to explore theme system and identify the realization of thematic progression based on Halliday's theory (1994) in undergraduate students' exposition texts at a university in Bandung. This study belongs to a non-experimental research design involving twelve exposition texts (six analytical and six hortatory exposition text) as the data of this study. There were three types of the Theme used by undergraduate students in their text namely Topical, Textual and Interpersonal in which the Topical Theme was the most frequent. In terms of theme markedness, of the two types of theme markedness namely unmarked theme and marked theme, the unmarked theme was dominant. As for the realization of thematic progression, there were three patterns used by undergraduate students; thematic reiteration, zig-zag, and multiple patterns. The thematic reiteration pattern was the most common pattern, followed by the zig-zag, and the multiple theme pattern. In terms of students' achievement, of the three categories namely high, middle, and low achievers, the high achiever undergraduate students were the most frequent in theme system and thematic progression. This means that the undergraduate students are able to write cohesive and coherent exposition text. It is recommended that the theme system and thematic progression are needed to be implemented in English language teaching to enhance students' reading and writing skills.;---Penelitian ini bertujuan untuk mengeksplorasi penggunaan ''Theme System" dan mengidentifikasi ''Thematic Progression" berdasarkan teori Halliday (1994) dalam teks eksposisi mahasiswa di sebuah universitas di Bandung. Penelitian ini termasuk dalam metode penelitian non-exprimental yang melibatkan data sebanyak dua belas teks eksposisi (enam teks analitikal dan enam teks hortatory eksposisi). Ada tiga tipe theme system yang digunakan oleh mahasiswa dalam teksnya; Topical, textual, dan interpersonal theme yang mana topical theme yang sering muncul di teks tersebut. Di area theme markedness, dari dua tipe theme markedness yakni unmarked theme dan marked theme, yang lebih dominan adalah unmarked theme. Sementara realisasai pada thematic progression, ada tiga pola yang digunakan oleh mahasiswa; Reiteration, zig zag, dan multiple pattern. Reiteration pattern yang sering muncul di dalam teks tersebut, diikuti oleh zig zag dan multiple pattern. Di area tingkat kemampuan mahasiswa, dari tiga kategori; kemampuan tinggi, menengah, dan bawah, mahasiswa yang berkemampuan tinggi yang paling banyak mucul theme system dan thematic progressionnya. Dari beberapah hal tersebut membuktikan bahwa mahasiswa mampu menulis teks eksposisi yang kohesiv dan koherensi nya baik. Oleh karena itu, Theme dan Thematic Progression perlu diimplementasikan dalam setiap pengajaran bahasa Inggris untuk meningkatkan keterampilan membaca dan menulis mahasiswa.